How to Make Use of Animation to Improve Primary School Students' English Achievement? - Nurdyansyah, Nurdyansyah; Mandarani, Vidya; Rais, Pandi (Universitas Muhammadiyah Sidoarjo, 2020)
One of the innovations in English Language Teaching is the use of moving images. This research aims to investigate how animation contribute to the students' achievement in their English class. A classroom action research was applied with 39 first grade students involved. Observation sheet, test and documentations were used to collect the data. Three components (reduction activity, data presentation and interpretation) were used to analyse the collected data. The results indicate that the use of animation can significantly enhance lower class of primary school students’ achievements in learning English. This can be measured through their average score improvement. This result suggests teachers use moving images in order to assist students’ progress in learning English. This study implies that teachers should equip themselves with a skill to create fun classroom activities through animation. HIGHIGHTS: The application of moving picture media in classroom activities can significantly improve students’ competence and achievement in learning English for first grade of second semester in Primary School. Teachers' digital literacy need to be heightened through their active contribution in workshop or other teacher professional development activities. This helps them to build their creativity to make more modification and development of animation.